Effects of Land Use Types on Selected Soil Properties in Central Highlands of Ethiopia - Daniel Jaleta Negasa (Applied and Environmental Soil Science)
Rapid land use changes have been observed in recent years in central Ethiopia. The shift from natural ecosystem to artificial ecosystem is the main direction of change. Therefore, this study was initiated to assess the effects of land use types on selected soil properties in Meja watershed, central highlands of Ethiopia. The randomized complete block design, including three adjacent land use types as treatments with three replications and two soil depths (0–15 and 15–30 cm), was applied in this study. There were significant differences in some soil properties among the three land use types. Lower soil pH and electric conductivity were observed in cultivated land soils than Eucalyptus woodlots soils. This has indicated the worsening soil conditions due to the shift from Eucalyptus woodlots to cultivated land. Less decomposition rate of the Eucalyptus leaves and debris collection for fuel could result in lowest soil organic carbon at the upper layer of Eucalyptus woodlot soils. However, the highest soil organic carbon at the lower layer was observed in Eucalyptus woodlot soils. The presence of highest soil potassium, cation exchange capacity, and exchangeable potassium in cultivated land soil was related to application of artificial fertilizers. Grassland soils have highest exchangeable sodium at the lower layer while highest soil carbon and sum cations at the upper layer, which can be related to the grass root biomass return and less surface runoff on grassland. There was the highest exchangeable sodium percentage on Eucalyptus woodlot soils at the upper layer; it can be due to the less surface nutrient movement and growth characteristics of the tree. The soils in cultivated land was shifted to more acidic and less electric conductivity.This shift can lead to soil quality deterioration that affects the productivity of the soils in the future.Nutrient leaching, application of artificial fertilizer, soil erosion, and continuous farming have affected the soil properties in cultivated land. The presence of highest exchangeable sodium percentage and lowest sum of cations at the upper layer of soil in Eucalyptus woodlot should be noted for management and decision makers. The previous negative speculations on Eucalyptus woodlots which can be related with the soil texture, soil moisture, bulk density, total nitrogen, exchangeable magnesium, calcium, and available sulfur should be avoided because there were no significant differences observed among the three land use types in the study area. The study recommends further studies on the effects of Eucalyptus on soil properties by comparing among different ages and species of Eucalyptus. Finally, planting of Eucalyptus on central highlands of Ethiopia should be supported by land use management decision.